A closed-form solution for buckling analysis of orthotropic Reddy plates and prismatic plate structures. (15th July 2019) - Ruocco, E.; Reddy, J.N.
Abstract: This paper presents an analytical solution for elastic buckling problems of thick, composite prismatic plates subjected to uniaxial or biaxial compressive loads. Based on Reddy's third-order shear deformation theory and the Green-Lagrange deformation measure, the governing equations and natural boundary conditions of the plate are derived using Hamilton's principle, and solved analytically using the Navier and Levy-type solution methods. A large number of configurations are analyzed, and the effects of geometric and material properties on the buckling of both isotropic and orthotropic prismatic plates, as well as transversely anisotropic sandwich plates, are determined with a reduced computational effort. A comparison with results available in the literature, also determined by considering alternative plate models, shows the accuracy of the proposed approach.